Jesus, presença em ausência: autorretrato como gênero expandido - Quintero, Jesus Enrique (2018)
This dissertation intends on bringing to light the need for an artist to create different ways, practices, strategies, and tactics in generating other aesthetic possibilities; overcoming boundaries and intertwining knowledge to break up with hardened structures, allowing because of that to be perceived as ridiculous by his contemporaries in the proposal of his own art, but acknowledging and accepting ridiculousness as a dynamic element creator of new possibilities - just as error, slowness, and difficulties can also create productive aesthetic results. I develop this research as a self-fiction narrative; where Jesus Enrique Quintero presents himself as artist and researcher - different identities -, analyzing the evolution of self-portrait as a subgenre from vanguards to post-modernity, pondering about its function and specificity, as well as its boundaries, attempting to enlarge concepts and understanding about language and the potency of performance as an aesthetic and social phenomenon, and possibilities of his own making through an investigative experience that can be of use to any other researcher, teacher, student and even a wider public, since life itself can be understood as performative action and construction. The general objective is: Analyze self-portrait as an expanding genre. And the specific objectives are: conduct a survey on different kinds of references, for instance, bibliographic references of texts, articles, essays, doctoral thesis, videos containing a critical analysis about self-portrait as an expanding genre beyond its traditional concept, from concepts of identity, representation, self-referentiality, autobiography, self-fiction, performance and video installation. Thinking about aesthetic dialogues between performance, literature and electronic art from a narcissistic aesthetic. Self-portrait as an expanding genre, understanding the expanding genre as extended to other medias.